Healthcare resource utilization and costs of outpatient follow-up after liver transplantation in a university hospital in São Paulo, Brazil: cost description study - Soárez, Patricia Coelho de; Lara, Amanda Nazareth; Sartori, Ana Marli Christovam; Abdala, Edson; Haddad, Luciana Bertocco de Paiva; D’Albuquerque, Luiz Augusto Carneiro; Novaes, Hillegonda Maria Dutilh (São Paulo Medical Journal, 2015)
CONTEXT AND OBJECTIVE: Data on the costs of outpatient follow-up after liver transplantation are scarce in Brazil. The purpose of the present study was to estimate the direct medical costs of the out-patient follow-up after liver transplantation, from the first outpatient visit after transplantation to five years after transplantation. DESIGN AND SETTING: Cost description study conducted in a university hospital in São Paulo, Brazil. METHODS: Cost data were available for 20 adults who underwent liver transplantation due to acute liver failure (ALF) from 2005 to 2009. The data were retrospectively retrieved from medical records and the hospital accounting information system from December 2010 to January 2011. RESULTS: Mean cost per patient/year was R$ 13,569 (US$ 5,824). The first year of follow-up was the most expensive (R$ 32,546 or US$ 13,968), and medication was the main driver of total costs, accounting for 85% of the total costs over the five-year period and 71.9% of the first-year total costs. In the second year after transplantation, the mean total costs were about half of the amount of the first-year costs (R$ 15,165 or US$ 6,509). Medication was the largest contributor to the costs followed by hospitalization, over the five-year period. In the fourth year, the costs of diagnostic tests exceeded the hospitalization costs. CONCLUSION: This analysis provides significant insight into the costs of outpatient follow-up after liver transplantation due to ALF and the participation of each cost component in the Brazilian setting.